DAYA SAING KOMODITAS LADA INDONESIA DI PASAR INTERNASIONAL (Studi Tentang Ekspor Lada Indonesia Tahun 2010-2014) - Dini Tri Kurnianto; Suharyono Suharyono; Kholid Mawardi (Jurnal Administrasi Bisnis, 2016)
The purpose of this study was to determine the competitiveness of Indonesian pepper commodities in the international market. The analysis is the analysis of Porter's Diamond Analysis, RCA, and ISP with qualitative and quantitative approaches. The results of this study are Indonesian pepper commodities lacks on competitiveness. This is evidenced by Indonesian human resources and natural resources are very abundant, but very lacking in technology, capital, and infrastructure. The weakness of related industries is very influential, structure and competition is very high with product diversification strategy. For the government and chance factors a very good. Indonesian pepper commodities has a comparative advantage with RCA value is still above Vietnam that has value 7.91, Indonesia with a RCA value 33.90. Indonesian Value ISP in 2014 period about 0.72 and it is still inferior to Brazil with ISP value about 0.99. Keywords : Competitiveness, Export, Pepper. ABSTRAK Tujuanapenelitian inidadalah mengetahuiudaya saingekomoditas ladakIndonesia di pasarnintenasional. Analisis yang digunakan adalah Analisis0Daya Saing0Berlian Porter,0RCA, dan0ISP dengan pendekatan kualitatif dan kuantitatif. Hasil penelitian ini adalah komoditas lada Indonesia tidak mempunyai daya saing kompetitif. Hal ini dibuktikan dengan SDM dan SDA Indonesia yang sangat melimpah, tapi sangat kurang dalam Teknologi, Modal,udanuInfrastruktur. Masih lemahnya industrioterkait sangat berpengaruh, strukturpdanykompetisi sangat tinggi dengan strategigdiversifikasisproduk. Untuk faktor9pemerintah dan3kesempatan sangat baik. Komoditas ladaIIndonesia mempunyaipkeunggulan komparatiftdengan nilaiiRCA 7,91 tapi Vietnamomasih diatas Indonesia dengan nilaihRCA 33,90. Nilai ISP Indonesia tahun 2014 sebesar 0,72 masih kalah dengan Brazil sebesar 0,99. Kata Kunci : Daya Saing, Ekspor, Lada